2016
DOI: 10.3390/ma9040259
|View full text |Cite
|
Sign up to set email alerts
|

Microparticles for Sustained Growth Factor Delivery in the Regeneration of Critically-Sized Segmental Tibial Bone Defects

Abstract: This study trialled the controlled delivery of growth factors within a biodegradable scaffold in a large segmental bone defect model. We hypothesised that co-delivery of vascular endothelial growth factor (VEGF) and platelet derived growth factor (PDGF) followed by bone morphogenetic protein-2 (BMP-2) could be more effective in stimulating bone repair than the delivery of BMP-2 alone. Poly(lactic-co-glycolic acid) (PLGA ) based microparticles were used as a delivery system to achieve a controlled release of gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 56 publications
0
18
0
2
Order By: Relevance
“…Previously, we have developed improved methods for growth factor delivery by decoupling release kinetics from polymer degradation by the inclusion of a more hydrophilic component, such as polyethylene glycol (PEG; White et al, ). The addition of an “in‐house” developed triblock copolymer, PLGA–PEG–PLGA provides additional control over polymer hydration to achieve sustained delivery (G. Kirby et al, ; White et al, )…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously, we have developed improved methods for growth factor delivery by decoupling release kinetics from polymer degradation by the inclusion of a more hydrophilic component, such as polyethylene glycol (PEG; White et al, ). The addition of an “in‐house” developed triblock copolymer, PLGA–PEG–PLGA provides additional control over polymer hydration to achieve sustained delivery (G. Kirby et al, ; White et al, )…”
Section: Introductionmentioning
confidence: 99%
“…Previously, we have developed improved methods for growth factor delivery by decoupling release kinetics from polymer degradation by the inclusion of a more hydrophilic component, such as polyethylene glycol (PEG; White et al, 2013). The addition of an "inhouse" developed triblock copolymer, PLGA-PEG-PLGA provides additional control over polymer hydration to achieve sustained delivery (G. Kirby et al, 2016;White et al, 2013) Therefore, the aim of this study was to encapsulate rhGDF6 in novel PLGA/PLGA-PEG-PLGA MPs to control its release over a defined timescale in vitro. Polymer MP delivery was investigated as this system offers high growth factor entrapment efficiency, the dry MPs have a long storage life, and MPs can be easily incorporated into injectable load-bearing hydrogel systems without significant detriment to mechanical properties [37].…”
Section: Introductionmentioning
confidence: 99%
“…Preliminary studies are reporting the use of NDs as multiple protein delivering vehicle [16]. Researchers have shown that the combined delivery of VEGF, PDGF and BMP-2 would lead to more efficient bone regeneration than BMP-2 alone based on the rationale that this would more closely mimic the biological events leading to bone formation [35]. The angiogenic factors would direct the processes for early vasculature, promoting BMP-2 induced osteogenic differentiation and bone formation.…”
Section: Future Perspectivementioning
confidence: 99%
“…También se ha estudiado la liberación controlada de diferentes factores de crecimiento en una matriz reabsorbible de policaprolactona en defectos óseo de 3 cm en tibia de ovino (Kirby et al, 2016). En su diseño experimental, comparó un grupo de MP de rhBMP-2 con MP de un conjunto de factores de crecimiento; factor de crecimiento vascular endotelial (VRGF), factor de crecimiento derivado de plaquetas (PFGF) y rhBMP-2.…”
Section: Uso De Rhbmp-2 Encapsulado En Mp De Plgaunclassified